Persepsi Masyarakat Petani Tentang Sekolah - Handayani, Luluk Dewi; Prihatin, Indah (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2023)
School is expected to provide knowledge and opportunities for students. However, the data showed that the level of education in rural areas is lower than in urban areas. This study aims to explore the perception of farmers about school as an institution. A qualitative approach with an Interpretative phenomenological analysis (IPA) is used as the analytical method. Interviews were used as a way of collecting data. This study involved three informants in an in-depth interview process. Those are farmers from Temanggung Regency (Central Java); SP (57), ER (49), D (42). This study found that school considered as social transformation agent and practical functional institution. The school activities are habit for farmer families, but on the other hand they realize that schools are social transformation agent for them.